Analisis perbandingan kinerja saham syariah antara DJIMI, FSTE GIIS, KLSESI, dan JII - Maharani, Novita Kusuma (Jurnal Ekonomi & Keuangan Islam, 2018)
This research investigates whether the difference of Sharia stock screening mechanism in some countries will influence the index and stock performance. Some countries have a tight screening policy and the other countries have a loose screening policy. This research investigates 4 Sharia indices DJIMI, FTSE GIIS, KLSESI, and JII since October 2012 until September 2014. This research shows that the performance of the Sharia stock index is not affected by how tight the screening process of that index. Although KLSESI index has the tightest stock screening policy, but the performance is not different with the Sharia stock which has loosest stock screening policy which is DJMI index. When we compare the return of each index, the performance of the 4 indices shows insignificant different. The performance of JII stock which has the looser stock screening policy is also not different with the KLSESI stock performance which has the tighter stock screening policy.